The Efficacy of Metacognitive Therapy: A Systematic Review and Meta-Analysis - Normann, Nicoline; Morina, Nexhmedin (Frontiers in Psychology, 2018)
Background Metacognitive therapy (MCT) continues to gain increased ground as a treatment for psychological complaints. During the last years, several clinical trials on the efficacy of MCT have been published. The aim of the current study was to provide an updated meta-analytic review of the effect of MCT for psychological complaints. Methods We conducted a systematic search of trials on MCT for young and adult patients with psychological complaints published until January 2018, using PsycINFO, PubMed, the Cochrane Library, and Google Scholar. Trials with a minimum of 10 participants in the MCT condition were included. Results A total of 25 studies that examined a variety of psychological complaints met our inclusion criteria, of which 15 were randomized controlled trials. We identified only one trial that was conducted with children and adolescents. In trials with adult patients, large uncontrolled effect size estimates from pre- to posttreatment and follow-up suggest that MCT is effective at reducing symptoms of the targeted primary complaint, anxiety, depression, and dysfunctional metacognitions. The comparison with waitlist control conditions also resulted in a large effect (Hedges’ g = 2.06). The comparison of MCT to cognitive and behavioral interventions at posttreatment and at follow-up showed pooled effect sizes (Hedges’ g) of 0.69 and 0.37 at posttreatment (k = 8) and follow-up (k = 7), respectively. Conclusions Our findings indicate that MCT is an effective treatment for a range of psychological complaints. To date, strongest evidence exists for anxiety and depression. Current results suggest that MCT may be superior to other psychotherapies, including cognitive behavioral interventions. However, more trials with larger number of participants are needed in order to draw firm conclusions.